Extragonadal aromatization increases with time after ovariectomy in rats - Chen Boying; Hao Junwei; Tian Zhanzhuang; Zhao Hong (BMC, 2005)
Abstract Background The circulating estrogen concentration elevated gradually along with time after ovariectomy in rats. To explore the source of the increased circulation estrogen, the extragonadal aromatization as well as the synthesis of androgen in the adrenal cortex of the ovariectomized rats was evaluated. Methods Female rats were divided into twelve groups: 1 month after ovariectomy (OVX1M), OVX2M, OVX3M, OVX4M, OVX5M, OVX6M; intact 1 month (INT1M), INT2M, INT3M, INT4M, INT5M, INT6M. The blood concentration of testosterone (T) was measured by radioimmunoassay. The mRNA expressions of P450 aromatase in the liver and subcutaneous abdominal (SA) adipose as well as the adrenal cytochrome P450 17 alpha hydroxylase/lyase (P450c17) were semiquantified by RT-PCR. The P450 aromatase protein expressions in the liver and SA adipose were detected by Western blot. Results The blood E2 concentrations increased gradually along with time after ovariectomy in the rats. The 58-kDa aromatase protein and mRNA expressions normalized to β-actin in the OVX6M rats' SA adipose tissues showed higher levels than those from corresponding tissues in the INT6M (p < 0.05). And the ratios of aromatase mRNA and protein to β-actin in the OVX6M rats' liver tissues increased significantly compared with those in the OVX1M rats (p < 0.05). The ratio of adrenal P450c17 to beta-actin in the OVX6M increased markedly, and was higher than OVX1M (p < 0.05), though the blood concentration of T decreased significantly in all the ovariectomized rats (p < 0.05). Conclusion Both the subcutaneous abdominal adipose tissues and the liver tissues contributed to the extragonadal aromatisation to promote the circulating E2 levels in the rats along with time after ovariectomy; the adrenal compensation might also be activated naturally.